Re-examination of the cranial osteology of the Arctic Alaskan hadrosaurine with implications for its taxonomic status - Takasaki, Ryuji; Fiorillo, Anthony R.; Tykoski, Ronald S.; Kobayashi, Yoshitsugu (PLOS ONE, 2020)
Hadrosaurid fossils from the Liscomb Bonebed (Prince Creek Formation, North Slope, Alaska) were the first dinosaur bones discovered from the Arctic. While the Prince Creek Formation hadrosaurids were long identified as Edmontosaurus, a member of the sub-clade Hadrosaurinae, they were recently assigned to a newly-erected taxon, Ugrunaaluk kuukpikensis. However, taxonomic status of the new taxon is ambiguous largely due to the immature nature of the specimens upon which it was based. Here we reexamine cranial elements of the Prince Creek Formation hadrosaurine in order to solve its taxonomic uncertainties. The Prince Creek Formation hadrosaurine possesses a short dorsolateral process of the laterosphenoid, one of the diagnostic characters of Edmontosaurus. The Prince Creek Formation hadrosaurine also shows affinity to Edmontosaurus regalis in the presence of a horizontal shelf of the jugal. Our morphological comparisons with other North American Edmontosaurus specimens and our phylogenetic analyses demonstrate that the Prince Creek Formation hadrosaurine should be re-assigned to Edmontosaurus. Because the Prince Creek Formation Edmontosaurus shows differences with lower latitude Edmontosaurus in a dorsoventrally short maxilla, presence of a secondary ridge on the dentary teeth, and the absence of the transverse ridge between basipterygoid processes of the basisphenoid, we consider that the Prince Creek Formation Edmontosaurus should be regarded as Edmontosaurus sp. until further discoveries of mature hadrosaurines from the Prince Creek Formation Bonebed and/or equivalently juvenile Edmontosaurus specimens from the lower latitudes allow direct comparisons. The retention of the Prince Creek Formation hadrosaurine as Edmontosaurus re-establishes a significant latitudinal distribution for this taxon. Despite the large latitudinal distribution of the taxon, the morphological disparity of Edmontosaurus is small within Hadrosaurinae. The small morphological disparity may be related to the relatively low latitudinal temperature gradient during the latest Cretaceous compared to present day, a gradient which might not have imposed significant pressure for much morphological adaptations across a broad latitudinal range.